Softstone : approaches to the study of chlorite and calcite vessels in the Middle East and Central Asia from prehistory to the present - Phillips, Carl S.,; Simpson, St John, (British Foundation for the Study of Arabia monographs ;, 2018)
Stone containers have been made and used in the Middle East for over eleven millennia where they pre-dated the invention of pottery and were widely traded. The appearance or properties of the stone helped govern how stone vessels were valued or used and many classes were strictly utilitarian, being used for storage, cooking or lighting. Others were decorated and at times they were considered valuable exotica, particularly in regions far removed from their source areas. The subject of stone vessels is attracting growing attention but this is the first attempt to bring together different approaches to the study of softstone vessels, particularly but not exclusively those carved from varieties of chlorite, and covering all periods from prehistory to the present.